Morphological Classification of Extraction Sockets and Clinical Decision Tree for Socket Preservation/Augmentation after Tooth Extraction: a Systematic Review - Gintaras Juodzbalys; Arturas Stumbras; Samir Goyushov; Onurcem Duruel; Tolga Fikret Tözüm (Stilus Optimus, 2019)
Objectives: The aim of present study was to review current literature concerning extraction socket classification immediately following tooth extraction and the rationales for socket preservation/augmentation procedures and with reference to it suggest novel clinical decision tree for extraction socket preservation/augmentation in aesthetic and non-aesthetic area. Material and Methods: The search protocol used the electronic MEDLINE (PubMed) and EMBASE databases for articles published between January 1 2009 and May 1 2019. The search included only human studies published in English. Outcomes were the indications and reasons for socket preservation/augmentation and classification of extraction sockets. Results: Ten studies fulfilled the inclusion criteria and were selected for the study. Although there are various types of extraction socket classifications none of them could completely evaluate all morphological parameters of alveolar ridge. Furthermore, present study revealed that indications for extraction socket preservation/augmentation have wider spectrum than socket morphology and are related to surrounding tissue anatomy or dental implantation operation indications and timing. Based on currently proposed extraction socket classifications and rationales, a novel decision tree for extraction socket preservation/augmentation immediately after tooth extraction in aesthetic and non-aesthetic area was suggested. Conclusions: The need of extraction socket preservation/augmentation immediately after tooth extraction should be determined by the aesthetic, functional and risk-related viewpoint. A novel clinical decision tree for extraction socket preservation/augmentation immediately after tooth extraction in aesthetic and non-aesthetic zones can be useful tool in socket preservation/augmentation procedures.